Operational definitions of sarcopenia should consider depressive symptoms. Issue 2 (12th March 2021) - Pasco, Julie A.; Sui, Sophia X.; West, Emma C.; Holloway‐Kew, Kara L.; Hyde, Natalie K.; Stuart, Amanda L.; Gaston, James; Williams, Lana J.
Abstract: Background: Originally, sarcopenia meant 'poverty of flesh', but recent operational definitions have brought poor muscle function to the fore. None has considered psychological well‐being. We compared muscle function components of the European Working Group on Sarcopenia in Older People Version 2 (EWGSOP2), the Foundation for the National Institutes of Health (FNIH), and the Sarcopenia Definitions and Outcomes Consortium (SDOC) algorithms for individuals with and without depressive and anxiety symptoms. Methods: This cross‐sectional study involved 348 women and 343 men (ages 60–96 years) from the Geelong Osteoporosis Study. Hospital Anxiety and Depression Scale scores for depression and anxiety ≥8 indicated depressive and anxiety symptoms. Measures included handgrip strength (HGS) and Timed Up and Go (TUG). Chi‐squared test identified inter‐group differences, and multivariable logistic regression identified poor muscle function in association with depressive or anxiety symptoms. Results: Twenty‐nine (8.3%) women and 28 (8.2%) men had depressive symptoms, and 83 (23.9%) women and 41 (12.0%) men had anxiety symptoms. For women, proportions with low HGS were greater for those with vs. without depressive symptoms according to EWGSOP2 and FNIH (37.9% vs. 10.7%) and SDOC (51.7% vs. 26.7%); low HGS/body mass index (44.8% vs. 15.7%); and slow TUG (12.5% vs. 1.4%) (all P  ≤ 0.011). In age‐adjusted models, women with depressive symptoms were two‐fold to five‐fold more likely to have low HGS by EWGSOP2 and FNIH {odds ratio [OR] 4.77 [95% confidence interval (CI) 1.83–12.45]} and SDOC [OR 2.59 (95% CI 1.10–6.07)], low HGS/body mass index [OR 3.92 (95% CI 1.69–9.07)], and 11‐fold more likely to have a slow TUG [OR 10.99 (95% CI 2.03–59.7)]. For men, a difference for low HGS for those with depressive symptoms was detected only for SDOC (64.3% vs. 40.0%, P  = 0.013), but this was explained by age [OR 1.99 (95% CI 0.84–4.71)]. No differences were detected for anxiety symptoms. Conclusions: Operational definitions should consider depressive symptoms, at least in women, at the time of muscle function evaluation.